Clinical and immune-related factors associated with exacerbation in adults with well-controlled generalized myasthenia gravis - Bi, Zhuajin; Zhan, Jiayang; Zhang, Qing; Gao, Huajie; Yang, Mengge; Ge, Huizhen; Gui, Mengcui; Lin, Jing; Bu, Bitao (Frontiers in Immunology, 2023)
Objectives To describe the clinical predictors and immune-related factors for exacerbation in adults with well-controlled generalized myasthenia gravis (GMG). Methods We conducted a retrospective analysis of 585 adults with well-controlled GMG from our institution to explore the risk factors for exacerbation. Furthermore, propensity score matching (PSM) was used to compare the proportions of lymphocyte subsets, and the levels of immunoglobulin, complement, and anti-acetylcholine receptor antibody (AChR-ab) in the peripheral blood of 111 patients with exacerbations and 72 patients without exacerbations. Results A total of 404 patients (69.1%) experienced at least one exacerbation, and the median (interquartile range) time to the first exacerbation was 1.5 years (0.8–3.1 years). Multivariable Cox regression analysis showed that age at onset, disease duration before enrollment, Myasthenia Gravis Foundation of America classification (MGFA) class III vs. class II, MGFA class IV-V vs. class II, AChR-ab levels, anti-muscle specific kinase antibody levels, thymus hyperplasia, prednisone plus immunosuppressants vs. prednisone treatment, and thymectomy were independent predictors for exacerbations [hazard ratio (HR) = 1.011, 1.031, 1.580, 1.429, 2.007, 2.033, 1.461, 0.798, and 0.651, respectively]. Propensity-matched analysis compared 51 patient pairs. After PSM, the peripheral blood proportions of CD3–CD19+ B cells, ratios of CD3+CD4+/CD3+CD8+ T cells, and AChR-ab levels were significantly increased, and the peripheral blood proportions of CD3+CD8+ T and CD4+CD25+CD127low+ regulatory T cells (Tregs) were significantly lower in patients with exacerbation than in those without exacerbation (all p < 0.05). Conclusion Myasthenia gravis (MG) exacerbations were more frequent in those patients with older onset age, longer disease duration, more severe MGFA classification, positive AChR-ab, and lack of combined immunotherapy or thymectomy treatment. On the other hand, CD3–CD19+ B cells, CD3+CD8+ T cells, Tregs, and AChR-ab in peripheral blood may be involved in the course of GMG exacerbation.